TANTANGAN PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM DALAM MENGHADAPI TANTANGAN KONTEMPORER - Rahmadillah Ansori; Cipto Handoko; Nur Widi Astuti (UNISAN JURNAL, 2024)
Islamic education today faces many complex problems that come from internal and external sources. It’s about how Islamic education can handle the problems and demands that arise from some of those factors. Islamic education must build a plan so as not to be left behind in the creation of relevant curricula and able to adapt to the change of times. The research aims to provide information on the challenges and demands faced by Islamic education in the modern era, as well as methods to respond to them through curriculum development. This article is included in a qualitative research based library research. The results of the research show that Islamic education today faces problems that originate from the internal and external areas. Islamic education faces internal challenges, such as achieving eight national educational standards, Indonesian population growth that increases demographic bonuses, and character problems. As part of the Islamic education effort to prepare human resources capable of meeting the demands of today’s expertise, the ultimate goal is to produce graduates who can survive and participate in the era of globalization. One of the goals of Islamic education is to prepare for future needs related to social issues, technological and information advances, the growth of creative and cultural sectors, and the internationalization of education into world-class universities.